Reintubation of patients submitted to cardiac surgery: a retrospective analysis - Shoji, Cíntia Yukie (Rev Bras Ter Intensiva, 2017)
OBJECTIVES: To analyze patients after cardiac surgery that needed endotracheal reintubation and identify factors associated with death and its relation with the severity scores. METHODS: Retrospective analysis of information of 1,640 patients in the postoperative period of cardiac surgery between 2007 and 2015. RESULTS: The reintubation rate was 7.26%. Of those who were reintubated, 36 (30.3%) underwent coronary artery bypass surgery, 27 (22.7%) underwent valve replacement, 25 (21.0%) underwent correction of an aneurysm, and 8 (6.7%) underwent a heart transplant. Among those with comorbidities, 54 (51.9%) were hypertensive, 22 (21.2%) were diabetic, and 10 (9.6%) had lung diseases. Among those who had complications, 61 (52.6%) had pneumonia, 50 (42.4%) developed renal failure, and 49 (51.0%) had a moderate form of the transient disturbance of gas exchange. Noninvasive ventilation was performed in 53 (44.5%) patients. The death rate was 40.3%, and mortality was higher in the group that did not receive noninvasive ventilation before reintubation (53.5%). Within the reintubated patients who died, the SOFA and APACHE II values were 7.9 ± 3.0 and 16.9 ± 4.5, respectively. Most of the reintubated patients (47.5%) belonged to the high-risk group, EuroSCORE (> 6 points). CONCLUSION: The reintubation rate was high, and it was related to worse SOFA, APACHE II and EuroSCORE scores. Mortality was higher in the group that did not receive noninvasive ventilation before reintubation.